Echocardiography assessment of right ventricular dysfunction during postoperative period following total correction of tetralogy of Fallot - Kabir, Rashadul; Hussain, M. Zahid; Islam, M. Tariqul; Chowdhury, Naharuma Aive Haider; Karim, Tahmina; Rahman, Arifur; Sharmin, Rubaba (International Journal of Contemporary Pediatrics, 2022)
Background: Despite major advances in intracardiac surgery since Lillehei and Varco reported the first tetralogy of Fallot (TOF) repair by an open-heart procedure in 1954, right ventricular (RV) dysfunction remains an important clinical problem during the postoperative periods following TOF correction. Methods: This was a cross-sectional study conducted at the department of paediatric cardiology in Bangabandhu Sheikh Mujib medical university (BSMMU), Shahbag, Dhaka in collaboration with national heart foundation hospital and research institute (NHFH and RI) Mirpur, Dhaka, Bangladesh during the period from July 2018 to June 2019. Ethical consideration was approved by the proper concerns. The final sample size was 49. Data analysis was carried out by using the social science (SPSS) version 23.0 windows software. Results: The study was conducted on 49 patients, comprising 30 males and 19 females’ children, and their mean age was 75.38±52.22 months. RV dysfunction global was 63.3% at 24 hours of operation, significantly reduced 49% and 32.7% at 7th and 30th POD respectively. Chi-square test was done where p<0.05. Global dysfunction was 13 (54.2) in ≤5 years, 18 (72.0) in >5 years aged patients. Conclusions: RV dysfunction was more frequent after 24 hours of the postoperative period then it gradually decreases over a period of time